A Pilot Study on Feasibility of Ultrashort Echo Time T2* Cartilage Mapping in the Sacroiliac Joints. Issue 5 (4th September 2021) - Wong, Tony T.; Quarterman, Patrick; Duong, Phuong; Rasiej, Michael J.; Wang, Runsheng; Jaramillo, Diego; Jambawalikar, Sachin R.
Abstract : Purpose: Assess feasibility of ultrashort echo time (UTE) T2* cartilage mapping in sacroiliac (SI) joints Methods: Prospective magnetic resonance imagings with UTE T2* cartilage maps obtained on 20 SI joints in 10 subjects. Each joint was segmented into thirds by 2 radiologists. The UTE T2* maps were analyzed; reliability and differences in UTE T2* values between radiologists were assessed. Results: Mean UTE T2* value was 10.44 ± 0.60 ms. No difference between right/left SI joints (median, 10.52 vs 10.45 ms; P = 0.940), men/women (median, 10.34 vs. 10.57 ms; P = 0.174), or different anatomic regions (median range 10.55–10.69 ms; P = 0.805). Intraclass correlation coefficients were 0.94 to 0.99 (intraobserver) and 0.91 to 0.96 (interobserver). Mean bias ± standard deviation on Bland-Altman was −0.137 ± 0.196 ms (limits of agreement −0.521 and 0.247) without proportional bias (β = 0.148, P = 0.534). Conclusions: The UTE T2* cartilage mapping in the SI joints is feasible with high reader reliability.